CONVERGENCES AND DIVERGENCES BETWEEN AN EFL TEACHER’S BELIEFS AND CLASSROOM PRACTICES IN TEACHING SPEAKING - Ainun, Nabila Hasri; Yusuf, Fazri Nur (Universitas PGRI Sumatera Barat, 2023)
Revealing teachers’ beliefs about teaching in EFL speaking contexts may help better teaching practice. This research was conducted to investigate a teacher’s belief about teaching speaking focusing on convergences and discrepancies between the beliefs and the practices in the classroom. Grounded in a qualitative case study with interviews and classroom observations, an experienced English teacher with more than 10 years of teaching speaking in English participated in the study. The results of the study indicated that the teacher paid more attention to fluency and gave practical speaking tips when the students encountered communication breakdowns. Further, the teacher generally practiced her belief in the classroom, even though she encountered some discrepancies. It was due to some students’ factors including students’ language proficiency and their affective factors. Therefore, it is essential for EFL teachers to systematically and regularly monitor the relations between their beliefs and practices through reflective practices in order to improve their everyday practice of teaching speaking in particular. It is further suggested that teachers get engaged in some reflective practices to bridge their beliefs and teaching practices and find out how the reflection can benefit their beliefs and instructional decisions.